Relation between chemical composition of Grateloupia doryphora (Montagne) Howe, Gymnogongrus griffithsiae (Turner) Martius, and abiotic parameters Relação entre composição química de Grateloupia doryphora (Montagne) Howe, Gymnogongrus griffithsiae (Turner) Martius e parâmetros abióticos - Paulo Nelo Medeiros Perfeto (Acta Botânica Brasílica, 1998)
In Grateloupia doryphora and Gymnogongrus griffithsiae the seasonal variation of their chemical compounds was studied, establishing a relation with the physical and chemical properties of seawater. High values of proteins in the studied species were detected during the winter, 28.88% in G. doryphora and 26.68% in G. griffithsiae, corresponding to the maximum period of ammonium concentration in the marine environment. The variation in carbohydrates content showed an inverse relation with the proteins, with a maximum of 54.72% in G. doryphora and of 55.36% in G. griffithsiae, both in summer, positively correlated with salinity and temperature of sea water. Lipids content was low in both species. In G. doryphora the values ranged between 0.81 and 1.30% and, in G. griffithsiae, from 0.71 to 1.50% of dry weight, showing a direct relation with the amount of nitrogen in the seawater. The maximum content of ashes, phosphorus and potassium occurred in autumn and winter, respectively, with 11.85%, 0.20%, 1.27% in G. doryphora, and 14.46%, 0.14%, 1.41% in G. griffithsiae. Foi estudado em Grateloupia doryphora e Gymnogongrus griffithsiae a variação sazonal de seus compostos químicos, estabelecendo uma relação com os parâmetros físico-químicos da água do mar. Durante o inverno foram detectados valores altos de proteína nas espécies estudadas, com 28,88 % em G. doryphora e 26,68 % em G. griffithsiae, correspondendo ao período de concentração máxima de amônio no ambiente marinho. A variação no conteúdo de carboidratos apresentou relação inversa à de proteínas. Os valores máximos de 54,72 % em G. doryphora e de 55,36 % em G. griffithsiae, ocorreram no verão, correlacionados positivamente com salinidade e temperatura da água do mar. Os conteúdos de lipídeos foram baixos em ambas as espécies. Em G. doryphora os valores variaram entre 0,81 e 1,30 % e em G. griffithsiae, de 0,71 a 1,50 % do peso seco, mostrando relação direta com a quantidade de nitrogênio na água do mar. O conteúdo máximo de cinzas, fósforo e potássio ocorreu no outono e inverno, respectivamente com 11,85 %, 0,20 % e 1,27 % em G. doryphora e 14,46 %, 0,14 % e 1,41 % em G. griffithsiae.